2002
DOI: 10.1021/bi012177r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differences Caused by Differentiation of 3T3-L1 Preadipocytes in the Presence of either Dehydroepiandrosterone (DHEA) or 7-Oxo-DHEA

Abstract: The effects of dehydroepiandrosterone (DHEA) and 7-oxo-DHEA on the cell size, adiposity, and fatty acid composition of differentiating 3T3-L1 preadipocyte cells are correlated with stearoyl-CoA desaturase (SCD) expression (mRNA and protein levels) and enzyme activity. Fluorescence-activated cell sorting shows that preadipocyte cells treated with methylisobutylxanthine, dexamethasone, and insulin (MDI) plus DHEA comprise a population distribution of predominantly large cells with reduced adiposity. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 58 publications
5
17
0
1
Order By: Relevance
“…Quite the opposite, palmitoleic acid (16:1 n-7) was reduced in s.c. and brown AT (and in serum, with marginal significance). These results are in agreement with those obtained by Imai et al (2001), who observed that DHEA stimulates oleate synthesis, resulting in increased 18:1 n-9 contents in liver, and with Gómez et al (2002), who also reported reduced 16:1 n-7 and elevated 18:1 n-9 in 3T3-L1 adipocytes treated with DHEA.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Quite the opposite, palmitoleic acid (16:1 n-7) was reduced in s.c. and brown AT (and in serum, with marginal significance). These results are in agreement with those obtained by Imai et al (2001), who observed that DHEA stimulates oleate synthesis, resulting in increased 18:1 n-9 contents in liver, and with Gómez et al (2002), who also reported reduced 16:1 n-7 and elevated 18:1 n-9 in 3T3-L1 adipocytes treated with DHEA.…”
Section: Discussionsupporting
confidence: 93%
“…By contrast, our experiment spanned a 13-week period that allowed us to observe a significant effect of DHEA on AT composition. Similarly to us, other authors have reported differences in FAs in muscle (Abadie et al 2001), liver (Imai et al 2001), and 3T3-L1 adipocytes (Gómez et al 2002) due to DHEA administration.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Protein Extraction and Western Blot-Proteins from 3T3-L1 cells were extracted as described previously (31). Briefly, the cell monolayer was washed with ice-cold PBS and subsequently scraped into 1 ml of ice-cold lysis buffer (50 mM Tris-HCl, pH 7.4, 150 mM NaCl, 1 mM EDTA, 0.25% sodium deoxycholate, 1% Nonidet P-40, 0.1% SDS, 1 mM phenylmethylmethanesulfonyl fluoride, 2 g/ml aprotinin, and 1 g/ml leupeptin).…”
Section: Methodsmentioning
confidence: 99%
“…The assay was carried out according to a published procedure [31]. Aliquots of excised muscles were weighed (ca.…”
Section: Methodsmentioning
confidence: 99%